Editorial: monitoring vedolizumab trough serum concentration in inflammatory bowel disease—following the fate of anti‐TNF‐alpha agents?. Issue 9 (11th April 2018) - Fragaki, M.; Karmiris, K.
Abstract : Linked Content This article is linked to Yacoub et al paper. To view this article visithttps://doi.org/10.1111/apt.14548 .